Conceptualizing School Improvements Dimension within the Context of School-Based Management - Ikhfan Haris (International Journal of Social Sciences & Educational Studies, 2016)
School Based Management has a strong emphasis on local decision making to ensure effective and continuous school improvement. There needs to be a strong focus on improved learning achievements for all students. For this to occur effectively, principals, school committees and supervisor (pengawas) need to continuously monitor and evaluate school performance. School Based Management is not an end in itself unless it can help foster an improved school culture, higher-quality decisions directed to improvement and above all, improvements in children‘s learning This paper deals with the conceptualizing school improvements dimension within the context of School Based Management. The introductory section of the paper describes the theoretical perspectives and the occasions of the conceptual framework of School-based Management. In addition, it followed by explanation about the key-points of quality improvement in the context of school integrated development. This paper also highlights the role of the principal in successful School Based Management in greater detail. Besides, the significance of the school culture in supporting the school improvement will also be presented. Finally it briefly explains the method and approach as well as the strategy to implement the plan of school integrated development.